Gradient-induced fuel consumption and CO₂ emission sensitivity: a comparative analysis of two and three-axle trucks on short uphill segments - Hakzah Hakzah; Abdul Rahman; Andriyani Andriyani; Jasman Jasman; Kasmaida Kasmaida (SINERGI, 2026)
Road freight transport significantly contributes to global energy use and greenhouse gas emissions, yet the influence of short uphill gradients on fuel consumption and CO₂ emissions remains insufficiently studied in Indonesia. While prior research has examined slope effects on long-haul operations, limited evidence quantifies sensitivity on short ascending segments (50–250 m) and compares two- and three-axle trucks. This study addresses this gap by applying a mathematical modeling framework that integrates technical parameters collected from the Datae Motor Vehicle Weigh Station (UPPKB Datae), Sidenreng Rappang Regency, South Sulawesi Province, Indonesia, with established fuel consumption and emission formulations. Gradient variations of 0–15% and travel distances of 50–250 m were analyzed, and fuel consumption results were converted into CO₂ emissions using IPCC guidelines. The findings reveal a sharp escalation in both fuel demand and emissions, with the slope increasing. At a 15% gradient and 250 m distance, CO₂ emissions rose by approximately 692% for two-axle trucks and 625% for three-axle trucks compared with the flat baseline. Although heavier trucks recorded higher absolute values, two-axle trucks exhibited greater relative sensitivity to changes in gradient. These results provide novel evidence on slope-induced inefficiencies in short segments, offering practical insights for eco-routing, operational planning, and gradient-sensitive decarbonization strategies in freight transport.